Training program for tuberculosis (TB) patients to improve referrals of presumptive TB cases and sputum in Denpasar, Bali, Indonesia - Putu Ayu Merry Antarina; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: Tuberculosis (TB) is a global healthproblem and one of the top ten causes of deaths in the world. TB case finding is an important component of TB control. In Indonesia, most case findings were done passively so that the referral coverage for TB sputum was lower than the target. This study aims to determine the effectiveness of training for TB patients as volunteers to increase the active referral of presumptive TB cases. Methods: The pretest-posttest design intervention study was conducted in five public health centers (PHCs) which had the highest number of TB patients in Denpasar. The intervention was carried out for seven weeks (February May 2020). A total of 35 TB patients, who were currently undergoing treatment at the PHCs, met the study criteria and willing to volunteer, were trained through meetings, discussions and demonstrations about the risk of TB transmission, contact investigations and how to collect sputum samples. Before and after the interventions, data on volunteers’ knowledge, the number of presumptive TB and sputum referrals by volunteers were collected through interviews and daily records. A regular reminder was sent in the form of a WhatsApp message once a week. Bivariate data analysis was performed with Chi-square and Wilcoxon Signed Rank Test. Results: Volunteers’ knowledge scores increased significantly after training, with a median score of 13.0 to 15.0 (p<0.001), and there was a significant difference in knowledge improvement amongthose who actively responded to regular reminders compared to those who were less active (p=0.002). A total of 31 presumptive TB cases were successfully referred during the study period (7 weeks). Volunteers managed to refer as many as 30 sputum preparations with good quality, but no positive sputum was found. Conclusion: Recruitment and training of TB patients as volunteers can increase the knowledge and skills of volunteers to identify and refer presumptive TB cases and quality sputum samples. More TB patients should be  trained as volunteers with a longer observation time to increase TB patient detectio